Ethical hacking and penetration testing guide - Baloch, Rafay (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
"This book introduces the steps required to complete a penetration test, or ethical hack. Requiring no prior hacking experience, the book explains how to utilize and interpret the results of modern day hacking tools, which are required to complete a penetration test. Coverage includes Backtrack Linux, Google reconnaissance, MetaGooFil, dig, Nmap, Nessus, Metasploit, Fast Track Autopwn, Netcat, and Hacker Defender rootkit. Simple explanations of how to use these tools and a four-step methodology for conducting a penetration test provide readers with a better understanding of offensive security. "--
Includes bibliographical references and index.
Keywords: Penetration testing (Computer security); COMPUTERS / Security / General; COMPUTERS / Networking / General; LAW / Forensic Science